KEBIJAKAN PEMERINTAH DALAM MENANGANI HARGA CABAI MERAH KERITING (capsicum annum L) (Studi Kasus Tinjauan Kebijakan Pemerintah pada Harga Cabai Merah keriting) di Sentra Produksi Kecamatan Cikajang dan Pasar Induk Kramat Jati Jakarta - Dety Sukmawati; Lies Sulistyowati; Maman H. Karmana; E kusnadi Wikarta (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
Price is a major factor, therefore, that the policy of raising agricultural output through price incentives to succeed, the government must know exactly how the response of supply / supply in the agricultural sector to price changes. The response will vary according to the type of commodity even among the farmers in the category of the same plant, depending on the purpose of the farmers do farming and economic conditions. The amount of supply response is also very informative for policy makers in evaluating policy -pembuat made in the field pertanian.Penelitian descriptively based on data from the Provincial Agriculture Office, 2015 West Java, Central Market Analysis of Agricultural Products Production Centers Cikajang Garutdan District Information Center Market Commodity Price Kramat Jati Jakarta. Policy directives coming horticultural commodities focused on chili, red onion and orange. Although the production of chili western Java had a surplus in terms of supply nationally, but the price of red chilli curls in particular always fluctuates, so if there is a price increase indicated a shortage of supply or shortage of production, so that the planting area three commodities were directed not at the park area, but the area outside the area and planting and planted not in the rainy season, but farmers are directed to plant in the dry season. The policy comprises: the pattern of production, regional development, institutional strengthening farmers, build supply chain and minimize supply chain, new technologies to increase production, the development of the field school, land registration and certification of products.